Retraduire Limbo : le syndrome littéraire du membre fantôme - Alice Ray (ReS Futurae)
The retranslation phenomenon is well known in the literary sphere, perhaps even necessary in the life of every translated work. In 2016, Limbo, by Bernard Wolfe, is retranslated in French, half a century after its first publication in 1952 and its first translation in 1955. This cynical novel offers an original way of writing and its content is also quite innovative: the novel paints a cybernetic posthumanity using both science fiction codes and Wolfe’s own elements of writing, which can raise some difficulties for the translators. This paper aims to analyse in a comparative way both the original text and the French translations. Thanks to a parallel and in-depth reading of the original work and the two translations, we will examine the amputation of the text in the first translation as well as the differences between the two French versions of the text. We will also try to understand the reasons of those differences in order to enlighten the translation issues which are inherent to the genre.